Augmented Passive Immunotherapy with P4 Peptide Improves Phagocyte Activity in Severe Sepsis. Issue 6 (December 2016) - Morton, Ben; Mitsi, Elena; Pennington, Shaun H.; Reiné, Jesús; Wright, Angela D.; Parker, Robert; Welters, Ingeborg D.; Blakey, John D.; Rajam, Gowrisankar; Ades, Edwin W.; Ferreira, Daniela M.; Wang, Duolao; et al.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Introduction: Antimicrobial resistance threatens to undermine treatment of severe infection; new therapeutic strategies are urgently needed. Preclinical work shows that augmented passive immunotherapy with P4 peptide increases phagocytic activity and shows promise as a novel therapeutic strategy. Our aim was to determine ex vivo P4 activity in a target population of patients admitted to critical care with severe infection. Methods: We prospectively recruited UK critical care unit patients with severe sepsis and observed clinical course (≥3 months postdischarge). Blood samples were taken in early (≤48 h postdiagnosis, n = 54), latent (7 days postdiagnosis, n = 39), and convalescent (3–6 months postdiagnosis, n = 18) phases of disease. The primary outcome measure was killing of opsonized Streptococcus pneumoniae by neutrophils with and without P4 peptide stimulation. We also used a flow cytometric whole blood phagocytosis assay to determine phagocyte association and oxidation of intraphagosomal reporter beads. Results: P4 peptide increased neutrophil killing of opsonized pneumococci by 8.6% (confidence interval 6.35–10.76, P  < 0.001) in all phases of sepsis, independent of infection source and microbiological status. This represented a 54.9% increase in bacterial killing compared with unstimulated neutrophils (15.6%) in early phase samples. Similarly, P4 peptide treatment significantly increased neutrophil and monocyte intraphagosomal reporter bead association and oxidation, independent of infection source. Conclusions: We have extended preclinical work to demonstrate that P4 peptide significantly increases phagocytosis and bacterial killing in samples from a target patient population with severe sepsis. This study supports the rationale for augmented passive immunotherapy as a therapeutic strategy in severe sepsis.